2020
DOI: 10.1111/asej.12220
|View full text |Cite
|
Sign up to set email alerts
|

Access to Antenatal Care in Laos: Analysis Using National Level Survey*

Abstract: Laos has the highest maternal mortality rate in Southeast Asia. The present study examines antenatal care and birth location in relation to the residence, household education levels, wealth, ethnicity, age and media interest of pregnant women. The logit and OLS regression results show that pregnant women living in urban areas and rural areas with roads, from wealthy families, in the Lao ethnic group and in the young age group are more likely to receive antenatal care and have professional health workers delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the present study, just 10⋅8 % of women belonging to the Hmong ethnic group reported ≥8 ANC contacts during their pregnancy, compared to 47⋅1 % of Lao women. Similarly, other studies have observed low ANC utilisation rates among women of ethnic minority populations in Lao PDR, especially among those with lower educational attainment (42,43) . Furthermore, ANC enhances hospital deliveries attended by skilled birth health workers, thereby reducing pregnancy and delivery-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the present study, just 10⋅8 % of women belonging to the Hmong ethnic group reported ≥8 ANC contacts during their pregnancy, compared to 47⋅1 % of Lao women. Similarly, other studies have observed low ANC utilisation rates among women of ethnic minority populations in Lao PDR, especially among those with lower educational attainment (42,43) . Furthermore, ANC enhances hospital deliveries attended by skilled birth health workers, thereby reducing pregnancy and delivery-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 60%
“…Hospital deliveries were the highest among women belonging to the Lao ethnic group in this study (48⋅1 %), while over a third of Hmong women gave birth at home. Language barriers, rural residence and greater distance to health facilities with a need for transportation can result in women of ethnic minorities not fully benefitting from ANC services (43,44) . Three quarters of the Laotian population live in remote rural areas, with a higher prevalence rate among minority ethnic groups, who thus have less access to services and infrastructure and higher rates of poverty and malnutrition (45) .…”
Section: Discussionmentioning
confidence: 99%